Characterization of the Vibrio anguillarum fur gene: role in regulation of expression of the FatA outer membrane protein and catechols. - Tolmasky, M E (1994)
The chromosomally encoded Vibrio anguillarum fur gene was characterized. The amino acid sequence of the Fur protein showed a very high degree of homology with those of V. cholerae and V. vulnificus. The degree of homology was lower, although still high, with the Escherichia coli and Yersinia pestis Fur amino acid sequences, while the lowest degree of homology was found with the Pseudomonas aeruginosa Fur protein. The C-terminal portion of Fur is the least conserved region among these Fur proteins. Within this portion, two regions spanning amino acids 105 to 121 and 132 to the end are the least conserved. A certain degree of variation is also present in the N termini spanning amino acids 28 to 46. Regulation of expression of the V. anguillarum fur gene by iron was not detected by immunoblot analysis. Mutations in the cloned fur gene were generated either by site-directed mutagenesis (the Lys-77 was changed to a Gly to generate the derivative FurG77) or by insertion of a DNA fragment harboring the aph gene in the same position. FurG77 was impaired in its ability to regulate a reporter gene with the Fur box in its promoter, while the insertion mutant was completely inactive. V. anguillarum fur mutants were obtained by isolating manganese-resistant derivatives. In one of these mutants, which encoded a Fur protein with an apparent lower molecular weight, the regulation of the production of catechols and synthesis of the outer membrane protein FatA were partially lost. In the case of another mutant, no protein was detected by anti-Fur serum. This derivative showed a total lack of regulation of biosynthesis of catechols and FatA protein by iron.